Front Roll Skill Level of Fifth Grade Students at Madrasah Ibtidaiyah Muhammadiyah Jenggotan, Andong, Boyolali - Dhany Sulaiman; Nur Subekti; Nurhidayat Nurhidayat (Ilmu Olahraga, 2026)
Abstract This study aimed to describe the level of front roll skills among fifth-grade students at Madrasah Ibtidaiyah Muhammadiyah Jenggotan, Andong, Boyolali Regency. A quantitative descriptive design with a survey method was employed, involving all 20 students as research participants through total sampling. Data were collected using a front roll practical test assessing three aspects: starting position, movement execution, and finishing position, and were analyzed descriptively using mean and standard deviation. The results showed a mean score of 6.70 (SD = 1.53), indicating that students’ front roll skills were generally in the low to moderate category. These findings suggest that students have not yet mastered the front roll skills optimally, highlighting the need for more structured and effective floor gymnastics instruction in physical education learning